CALOTROPIS PROCERA LEAF AND SEED EXTRACTS AS AN EFFECTIVE AGENTS AGAINST THE LARVAE OF CULEX QUINQUEFASCIATUS - MANIMEGALAI, K.; DHIVYA, R.; DHANALAKSHMI, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The larvicidal activity of leaf and seed extracts of Calotropis procera against the immature stages of Culex quinquefasciatus was determined. The larval mortality was observed after 24 h exposure. Ethanol extract of C. procera seed was found to have high larvicidal and pupicidal potency.